How Expoerts Decide: Preferences or Private Assessments on a Monetary Policy Committee? - Stephen Hansen; Michael McMahon; Carlos Velasco Rivera (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using voting data from the Bank of England, we show that different individual assessments of the economy strongly influence votes after controlling for individual policy preferences. We estimate that internal members form more precise assessments than externals and are also more hawkish, though preference differences are very small if members vote strategically. Counterfactual analysis shows that committees add value through aggregating private assessments, but that gains to larger committees taper off quickly beyond five members. There is no evidence that externals add value through preference moderation. Since their assessments also have lower precision, mixed committees may not be optimal.
Keywords: E52; E58; D78; 330; committees; monetary policy